Efficacy of Long-Term Treatment of Autosomal Recessive Hypercholesterolemia With Lomitapide: A Subanalysis of the Pan-European Lomitapide Study - D’Erasmo, Laura; Giammanco, Antonina; Suppressa, Patrizia; Pavanello, Chiara; Iannuzzo, Gabriella; Di Costanzo, Alessia; Tramontano, Daniele; Minicocci, Ilenia; Bini, Simone; Vogt, Anja; Stewards, Kim; Roeters Van Lennep, Jeanine; et al. (Frontiers in Genetics, 2022)
Backgroundand aim: Autosomal recessive hypercholesterolemia (ARH) is a rare autosomal recessive disorder of low-density lipoprotein (LDL) metabolism caused by pathogenic variants in the LDLRAP1 gene. Like homozygous familial hypercholesterolemia, ARH is resistant to conventional LDL-lowering medications and causes a high risk of atherosclerotic cardiovascular diseases (ASCVDs) and aortic valve stenosis. Lomitapide is emerging as an efficacious therapy in classical HoFH, but few data are available for ARH. Results: This is a subanalysis carried out on nine ARH patients included in the Pan-European Lomitapide Study. The age at starting lomitapide was 46 (interquartile range (IQR), 39.0–65.5) years, with a median treatment duration of 31.0 (IQR 14.0–40.5) months. At baseline, four (44.4%) patients had hypertension, one (11.1%) had diabetes mellitus, two (22.2%) were active smokers, and five (55.5%) reported ASCVD. The baseline LDL-C was 257.0 (IQR, 165.3–309.2) mg/dL. All patients were on statins plus ezetimibe, three were receiving Lipoprotein apheresis (LA), and one was also receiving proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i). The addition of lomitapide (mean dose, 10 mg) resulted in the achievement of a median on-treatment LDL-C of 101.7 mg/dL (IQR, 71.3–138.3; 60.4% reduction from baseline), with a best LDL-C value of 68.0 mg/dL (IQR, 43.7–86.7; 73.5% reduction from baseline). During follow-up, one patient stopped both PCSK9i and LA. Recurrence of ASCVD events was reported in one patient. The median on-treatment aspartate transaminase and alanine transaminase values were 31.1 (IQR, 22.6–48.3) U/L and 31.1 (IQR, 27.2–53.8) U/L, respectively. Among six ARH patients with available fibroscan examination, liver stiffness values recorded at the last visit were within the normal range (median, 4.7 KPa; IQR, 3.6–5.3 KPa). Conclusion: Lomitapide is effective and safe in ARH therapy as well as in classical HoFH.